Nord-Atlantischer Ozean / herausgegeben vom Reichs-Marine-Amt, 1911 - Germany. Reichs-Marine-Amt (Berlin : Reichs-Marine-Amt, 1928)
Kleine Berichtigungen: . 1928 Relief shown by hachures and spot heights. Depths shown by soundings and isolines.; "Nr. 383 (Tit. VI Nr. 1) Klasse 7."; Includes 11 x 9 cm paste-over at Ungava Bay, northern Quebec Grayscale; 1:12,000,000